Influence of Visual Composition on Graphic Design for Signage: Preference Analysis - Martín Martín, Irene; Sánchez Sánchez, María (Street Art & Urban Creativity, 2025)
This study seeks to investigate the extent to which composition, considered the graphic designer's most important tool for controlling the expression of the message, conditions the recipient's response (specifically, to proposals based on these two opposing formulas: balance and tension). Based on the ad hoc design of nine pairs of posters, a quantitative survey was conducted with a sample of 101 participants. The results show a significant influence of visual composition on the audience's response, which, in all age groups, overwhelmingly favours graphic solutions that emphasise greater balance or levelling.